ROLE OF PLANT EXTRACT IN THE INHIBITION OF DENTAL CARIES: Life Science - Dentistry - SHARMA, DEEPAK; JAIN, AKANSHA; AHUJA, SVECHHA; SACHDEVA , PRANSHU (International Journal of Life Science and Pharma Research, 2018)
Oral diseases are major health problems with dental caries and periodontal diseases among the most important but preventable infectious diseases. Oral health influences the general quality of life and poor oral health is linked to chronic conditions and systemic diseases. Oral diseases and the oral microbiota are well defined. There are over 750 species of bacteria that responsible the oral cavities, a number of which are implicated in oral diseases. The expretion of dental caries involves acidogenic and aciduric Gram-positive bacteria (mutans streptococci, lactobacilli and actinomycetes) and anaerobic Gram-negative bacteria (Porphyromonasgingivalis, Actinobacillus, Prevotella and Fusobacterium) have been linked to periodontal diseases. recent investigations oral disease, increased resistance by bacteria to antibiotics, adverse effects of some antibacterial agents currently used in dentistry and financial considerations in developing countries, in present situation need alternative safe, effective and economic treatment. Some of commercial drugs can unbalance oral flora and have adverse side-effects such as vomiting, diarrhea and tooth staining. Hence, the investigation for alternative phytochemicals isolated from plants used as alternatives medicines. This review covers recent development and investigations in plant extracts, phytochemicals and phytocompounds that control and kill the oral pathogens.